PREVENTION AND TREATMENT OF DOMESTIC VIOLENCE IN LEGAL PERSPECTIVE - Samuel Saut Martua Samosir; Gautama Budi Arundhati; Firman Floranta Adonara (UNEJ e-Proceeding, 2022)
This community service is entitled "Prevention and Handling of Domestic Violence from a Legal Perspective". In family life it is undeniable that conflict can occur in family relationships, conflict resolution should be resolved properly by realizing and understanding the feelings, personality and emotional control of each family member so that happiness in the family is realized. Healthy conflict resolution occurs when each family member does not prioritize personal interests, look for the root of the problem and make solutions that are mutually beneficial to family members through good and smooth communication. But on the other hand, conflicts that exist in the family, can happen badly so that it can lead to domestic violence (KDRT). This outreach activity was carried out using the problem inventory method, lectures, discussions and direct questions and answers with the participants. This activity was successful and has the potential to be followed up into a more concrete and contributive agenda. This community service was carried out on January 27, 2022 at the Head of the Muslimat Nahdahtul Ulama Branch of Karangpring Village, Sukorambi District, Jember Regency. The form of the activity is counseling, by providing socialization on Law Number 23 of 2004 concerning the Elimination of Domestic Violence, with the aim of forming the public to know and understand the law while at the same time fostering community sensitivity and solidarity. Keywords: domestic violence, prevention, solidarity